STRATEGICZNE ZNACZENIE METALI ZIEM RZADKICH - Daria Wiejaczka; Witold Wilczyński (Przegląd Geopolityczny)
Rare earths are materials that have become a strategic resource in the last two decades. Although their market is microscopic compared to other mining and metallurgical products, they are on the list of so-called critical raw materials both in the European Union and in the United States of America. This is because small amounts of these metals are necessary for the development of the most modern industries, important from the point of view of the energy and digital transformation process and the production of modern types of weapons. Unlike other mining raw materials that are offered by numerous suppliers, the rare earth metal market has been effectively monopolized by China. The aim of the article is to explain the importance of rare earths in the modern economy, the circumstances and reasons for the control of the market of these materials by a single power, as well as the possible ecological, economic and geopolitical consequences of this uncomfortable situation for the West. Considering the consequences of the Chinese monopoly in the form of destabilizing the economic situation and the possible threat to security on a global scale, the authors point to possible steps that can be taken by Western powers and their societies in order to diversify supplies of rare earth metals.